Essential oil of Croton zehntneri prevents electrophysiological alterations in dorsal root ganglia of streptozotocin-induced diabetes mellitus in rats - Francisco Walber Ferreira-da-Silva; Kerly Shamyra da Silva-Alves; Andrelina Noronha Coelho-de-Souza; José Henrique Leal-Cardoso (Phytomedicine Plus, 2023)
Croton zehntneri is an aromatic shrub, native to Northeast Brazil, where it is used in folk medicine. The essential oil of C. zehntneri (EOCz) has shown potent antioxidant and anti-inflammatory activities. Our aim was to investigate the beneficial effect of EOCz on electrophysiological changes in dorsal root ganglia (DRG) of rats with streptozotocin-induced diabetes mellitus (DM). DRG excitability and passive and active membrane properties were studied in control and DM-induced rats. Intracellular recording in current-clamp mode with sharp microelectrode was used. For Na+ channel investigation, patch-clamp recording in whole-cell mode was used. DM caused depolarizations (from -60.6 to -55.0 mV) of resting membrane potential without alteration of cell membrane input resistance. Also, it showed a tendency towards a decrease in rheobase and a tendency for increase in excitability, which was confirmed by increase in Na+ current (from -113.6 to -178.3 pF/pA). EOCz did not reverse the hyperglycemia of DM. Regardless of that, upon oral treatment, EOCz prevented neuronal alterations. EOCz was demonstrated to have low toxicity. The preventive effects of EOCz on neuronal changes coupled with its low toxicity make EOCz a potential candidate for a type of treatment of diabetic neuropathy complementary to therapy with hypoglycemic agents.